History's forgotten war stories - Slingerland, Janet (Hidden history (12 Story Library (Firm)), 2019)
Presents twelve little-known war stories from history that changed the course of world events. Includes a fact sheet, critical thinking questions, color photographs, a glossary, and further resources.